Table of Content - - (Journal of Curriculum and Teaching Methodology, 2025)
Table of Content: 1. Factors Influencing Mathematics Achievement among Saudi Students Compared to High-Performing Countries in TIMSS Dr. Mohammed Humaydan Alhisony, Prof. Mohammed Sant Alharbi 2. A teaching program based on the Authentic Instruction approach and its effectiveness in developing health awareness and future thinking skills among second-grade students in science Dr. Maryam Abdu Kariri, Prof. Hanan Abdul-Rahman Al-Arini 3. The effect of challenge-based learning on developing algebraic thinking skills among third-year middle school female students Ms. Lulwah Abdullah Al-Fahd, Co-Prof. Khaled Mohammed Al-Sharif 4. A Proposed Concept for a Teaching Strategy Based on the Schwartz Model to Develop Syntactic (Nahwi) Thinking Skills Among Secondary School Female Students Ms. Khadijah Atiah Falih Al-Huzali 5. Assessment for Learning Practices among Outstanding Science Teachers during the COVID-19 Pandemic: A Case Study in the Sultanate of Oman Ms. Sajda Ahmad Abdullah Al-Khaburi, Dr. Huda Ali Said Al-Hosni 6. Evaluating the Current State of the Life and Family Skills Curriculum for Third-Grade Intermediate Students in Light of Constructivist Theory Principles Ms. Nada Abdel-Aziz Al-Maashouq , Co-Prof. Manal Abdel-Rahman Al-Shabl 7. Content analysis of the human body systems course for the third secondary grade in light of creative thinking skills Ms. Haya Abdulaziz Nasser Bin Ghaith 8. The effectiveness of the Frayer Model in teaching grammar concepts to middle school students Mr. Firas Ahmad Shawakh